Upaya Meningkatkan Hasil Belajar Siswa pada Tema Pertumbuhan dan Perkembangan Makhluk Hidup melalui Model Discovery Learning di Kelas III SD Negeri 77/X Parit Culum I Semester Ganjil Tahun Pelajaran 2022/2023 - Syamsiah Syamsiah (Journal on Education, 2022)
This study aims to disclose information and discuss the Efforts to Improve Student Learning Outcomes on the Theme of Growth and Development of Living Things Through the Discovery Learning Model in Class III SD Negeri 77/X Parit Culum I Odd Semester 20022/2023 Academic Year. This research is included in the type of classroom action research (CAR). This research was conducted in This research was carried out at SD Negeri 77/X Parit Culum I. The time of this research was carried out in the odd semester of the academic year 2022 - 2023 starting in August 2022. The subjects in this study were grade III students, totaling 20 people. The research procedure consisted of two cycles with four stages of research starting from planning, implementation, observation and reflection. Data collection in this study was carried out using observation sheets, tests, documentation and field notes. The data analysis technique used in this research is using the percentage formula. The results of this study indicate that using the discovery learning model can improve student learning outcomes on the theme of growth and development of living things in class III SD Negeri 77/X Parit Culum I Odd Semester 20022/2023 Academic Year. This is evidenced by the students' mastery in learning starting from the pre-cycle, cycle I and cycle II which have increased by 35%, 50% and 95%.